الضرب دلالته وأنواعه في القرآن الكريم - علي، لؤي طارق (جامعة البصرة - كلية التربية للعلوم الإنسانية, 2018)
إِن مادة (ضَرَبَ) لها معان ودلالات عدة في النص القرآني، فتارة تأتي للإمعان في دلالتها المعروفة في النظم الاجتماعية، التي تثير من وقع عليه الضرب بانفعالات عدة ينتج عنها ردة فعلٍ ما، وتارة تخرج إلى الأمور المجازية غير الحقيقية؛ لان تعدد المعاني يدعونا إلى النظرِ والتأمل في طبيعة الكلمة وبنيتها في تعددية الدّلالات، وسوف يسلط البحث الضوء على هذه الدلالات؛ لكي نتعرف على ماهية (الضرب) وحقيقته في السّياق القرآني.
The content of DaRaba (hit) has many meanings and references in the Qura'nic text. Once, its reference is connected to the social systems that irritate the one who has been hit and the psychological reactions that result from it. Another time, it is connected to the metaphorical and unreal matters for the word has a wide range of meanings. This leads us to meditate upon the nature of the word and its morphology and multiplicity of meanings. The research will shed light on this multiplicity of reference to know the reality of Al Darb (hitting) in the Qura'nic text.
Keywords: القرآن الكريم -- ألفاظ القرآن -- تفسير القرآن